Lifestyle behaviours or socioeconomic characteristics? Gender differences in covariates of BMI in Hungary - E. Jarosz (Wiley, 2018)
Summary Objective Lifestyle behaviours are everyday activities that result from individual's values, knowledge, and norms shaped by broader cultural and socioeconomic context. These behaviours affect body weight as well as overall health and are influenced by a number of social characteristics. The aim of this paper was to examine the net effects of lifestyle behaviours and socioeconomic factors on body mass index (BMI), and how these differed by gender. Methods This study used the 2009/2010 Hungarian Time Use Survey combining behavioural records, background information, and measures of self‐reported health and weight. The sample (n = 7765) was representative for the Hungarian population. Multivariate linear OLS regression models were employed to analyse the net effects of lifestyle and sociodemographic variables. Results Daily behaviours were associated with BMI for women, but not for men, except for smoking. Meals frequency and duration of sleep had negative effects on female BMI, whereas duration of TV viewing had a positive effect. Occupational class was associated with male BMI, but not with female. The strong negative effect of smoking was significant for both genders. Conclusions Lifestyle behaviours were linked with female BMI, with socioeconomic characteristics impacting on male BMI. These results suggest that a gender‐specific approach may be appropriate to address obesity issues in the Hungarian population.